Transition Temperatures of Thermotropic Liquid Crystals from the Local Binary Gray Level Cooccurrence Matrix. (27th December 2012) - Sastry, S. Sreehari; Kumari, T. Vindhya; Rao, C. Nageswara; Mallika, K.; Lakshminarayana, S.; Tiong, Ha Sie
Abstract : This paper presents a method which combines the statistical analysis with texture structural analysis called Local Binary Gray Level Cooccurrence Matrix (LBGLCM) to investigate the phase transition temperatures of thermotropic p, n -alkyloxy benzoic acid (n OBA, n = 4, 6, 8, 10 and 12) liquid crystals. Textures of the homeotropically aligned liquid crystal compounds are recorded as a function of temperature using polarizing optical microscope attached to the hot stage and high resolution camera. In this method, second-order statistical parameters (contrast, energy, homogeneity, and correlation) are extracted from the LBGLCM of the textures. The changes associatedwiththe values of extracted parameters as a function of temperature are a helpful process to identify the phases and phase transition temperatures of the samples. Results obtained from this method have validity and are in good agreement with the literature.